2002
DOI: 10.1038/sj.bmt.1703704
|View full text |Cite
|
Sign up to set email alerts
|

Progressive multifocal leukoencephalopathy after stem cell transplantation, unsuccessfully treated with cidofovir

Abstract: Summary:We report a patient with progressive multifocal leukoencephalopathy (PML) after autologous stem cell transplantation (SCT) for non-Hodgkin's lymphoma (NHL). This is an unusual association, and to date only seven cases have been reported. This is the first case of PML after SCT treated with cidofovir, and the fifth case treated with this drug in a patient without human immunodeficiency virus (HIV) infection. In the previous four patients treated with cidofovir the outcome was discouraging, as was the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 19 publications
0
24
1
Order By: Relevance
“…There are eight reported cases of PML after autologous HCT [17][18][19][20][21][22][23] (Table 2). The median age of autograft recipients was 44 years (range: 31-60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are eight reported cases of PML after autologous HCT [17][18][19][20][21][22][23] (Table 2). The median age of autograft recipients was 44 years (range: 31-60).…”
Section: Discussionmentioning
confidence: 99%
“…Cidofovir was administered as monotherapy to a patient with a CD4 count of 535/mm 3 without clinical benefit. 18 Neurological complications are not considered among the most important causes of morbidity and mortality following HCT. Nonetheless, Gallardo et al 24 demonstrated a 37% incidence of neurologic symptoms in allograft recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation could be that the association between Hodgkin disease and PML is already well known and therefore not worth reporting. In contrast, after 1990, its appears that LPDs-associated PML is largely restricted to two groups of severely T-cell immunosuppressed patients: B-CLL patients who had received purine analogues [30,33,[35][36][37][39][40][41][42][46][47][48] and heavily pretreated patients with aggressive non-Hodgkin lymphoma after HDT/HSCT [29,31,34,[43][44][45]49].…”
Section: Discussionmentioning
confidence: 99%
“…One patient who survived was treated with intravenous immunoglobulins [33]. Cidofovir has been used in 6 cases without improvement [35,41,[43][44][45]48]. This is not surprising because most experts consider that this agent plays no role in the treatment of established PML [66].…”
Section: Discussionmentioning
confidence: 99%
“…The patient required long-lasting steroid treatment and although bronchiolytis evolved with success, he died 9 months later because of PML due to JC virus, unresponsive to treatment with cidofovir. 5 All patients were in remission when these complications were diagnosed.…”
mentioning
confidence: 99%